New Stage of the Innovative Performance of Israel: Progress or the Loss of Leadership? - N. V. Zakharova; A. V. Labudin (Управленческое консультирование)
The purpose of this study is to analyze and formulate the main features of the Israel economy and the changes that have occurred in the last few years. As everybody knows, Israel once has turned into one of the most innovative countries in the world. To achieve this goal, the article clarifies what Israel’s path to the “startup economy” was, what explains this “economic miracle”. The authors attract a large amount of statistical and factual material, on the basis of which they formulate the main features, problems and prospects of the socio-economic development of this state. The article uses methods of analysis and synthesis, generalization, observation, measurement, analogy, modeling. As a result of the study, it is proved that the “economic miracle” of Israel was natural and was based on a number of economic, social and political reasons. At the same time, Israel, in addition to its strengths in the economy in general and in innovation in particular, also has weaknesses and unresolved problems. As the conclusions of the study, it can be noted that the current transformation of the innovation system and the technological ecosystem does not indicate the loss of leadership by this country, but rather indicates the development of new approaches to economic development, both strategies and tactics.